2010
DOI: 10.3354/ame01395
|View full text |Cite
|
Sign up to set email alerts
|

Microcystins do not provide anti-herbivore defence against mixotrophic flagellates

Abstract: While most experiments investigating zooplankton grazing on harmful cyanobacteria have been carried out with metazoan plankton, several protozoa can also feed efficiently on cyanobacteria. We investigated grazing by the mixotrophic flagellate Ochromonas sp. on the toxic cyanobacterium Microcystis aeruginosa. Ochromonas sp. grew rapidly on M. aeruginosa and had a strong impact on the population density of its prey. However, specific growth rates of Ochromonas sp. decreased over time, possibly indicating a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 43 publications
3
33
3
Order By: Relevance
“…The mixotroph feeds upon the autotroph with a Holling type III functional response, in 138 accordance with the experimental data of Wilken et al (2010): 139…”
Section: Theory 99supporting
confidence: 80%
“…The mixotroph feeds upon the autotroph with a Holling type III functional response, in 138 accordance with the experimental data of Wilken et al (2010): 139…”
Section: Theory 99supporting
confidence: 80%
“…However, no induction of toxins was found in response to direct and indirect exposure to the mixotrophic flagellate Ochromonas sp. (Wilken et al, 2010).…”
Section: Chemical Defences In Phytoplanktonmentioning
confidence: 99%
“…Previous studies have reported as possible grazers of Microcystis: protists (Cole and Wynne 1974;Dryden and Wright 1987), rotifers (Snell 1980;Fulton and Paerl 1987), crustacean zooplankton (Hanazato and Yasuno 1984;Jarvis et al 1987), and fish (Moriarty 1973;Kawanabe and Mizuno 1989;Miura 1990). There are only a limited number of rotifers, crustaceans, and fish that graze on Microcystis, but various protistan species have been shown to do so (Zhang et al 1996;Nishibe et al 2002Nishibe et al , 2004Kim et al 2006;Wilken et al 2010). Thus, it is possible that the wax and wane of a Microcystis bloom are dependent on grazing by protists.…”
Section: Introductionmentioning
confidence: 93%